PERBANDINGAN GAYA MENGAJAR KOMANDO DENGAN GAYA MENGAJAR DISKOVERI TERHADAP HASIL BELAJAR SHOOTING DALAM PEMBELAJARAN BOLA BASKET - Sampurno, Hari Wibowo (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
The purpose of this study is to improve and improve the quality of shooting learning. The research hypothesis proposed is "the style of teaching discovers greater influence compared to the command teaching style of learning outcomes of shooting in basketballgames". The research method used was an experimental method, with the research design using posttest only control group design. The study population was vocational student. Affordable population is 205 class XI Pelita Bandung students, totaling 205 students. The sampling technique uses propotional randomized sampling technique. The research sample of 40 female students, randomly and proportionally divided into two groups, namely group A and group B. Group A is students who are taught in the command teaching style and group B is students who are taught in the style of discovers teaching. Based on the percentile value for the ttable distribution at the significance level Î±= 0.05 with (n1 + n2 -2) = 38, the price of t (0.95) = 1.68, while the t-test results =2.8. So thus the value of t is greater than the table value then Ho is rejected. It can be interpreted that the teaching style of cover (xÌ…= 10.05, s = 6.19) has a greater influence compared to the command teaching style (xÌ…= 7.9, s = 4.87) on the learning outcomes of shooting a basketball.